Authority in Arctic governance: changing spheres of authority in Greenlandic offshore oil and gas developments - Coco Smits; Jan Tatenhove; Judith Leeuwen
The Arctic has rapidly transformed from a “frozen desert” into a theater for high-level politics. Climate change and socioeconomic interdependencies bring the World more and more to the Arctic and vice versa. Increased geological knowledge, new technologies, and high-energy prices make it possible to develop oil and gas resources in the Arctic; however, the effectiveness of oil spill response techniques remains a key concern. To understand oil and gas exploration in the Arctic governance setting, and especially the authority of Greenland, we combine a multi-level governance framework with the concept sphere of authority from post-international theory. The Arctic sphere of authority on oil and gas consists of many different governance arrangements, of which the most well-known governance arrangement is the Arctic Council. This paper focuses on the authority of Greenland in the changing oil and gas governance arrangements in the Arctic. Crucial is the changing Danish–Greenlandic relationship, in which the development of a Greenlandic oil and gas sector is seen as a tool to become financially independent. It can be concluded that the capacity of the Greenlandic government and civil society actors should be the primary guideline for the pace in which oil and gas activities are being developed. Taking this approach will ensure that the Greenland is retaining its central position and high degree of influence on the governance of oil and gas development in its country. Otherwise, it will lose influence and benefits will flow elsewhere. Copyright Springer Science+Business Media Dordrecht 2014 Nested governance arrangements, Spheres of authority, Hydrocarbon development, Arctic Council, Institutional capacity, Greenland